Microbial levels on street foods and food preparation surfaces in Mangaung Metropolitan Municipality - Malerato Moloi; Gaofetoge G. Lenetha; Ntsoaki J. Malebo (AOSIS, 2021)
Background: The street food sector has become an important component of the food distribution system in many cities in both developing and industrialised countries, particularly for midday meals. However, certain street food can pose a significant risk to consumers because of microbiological contamination. Aim: The aim of this study was to determine the microbial levels of street foods and preparation surfaces in Mangaung Metropolitan Municipality. Setting: The study selected study setting was vending sites close to taxi ranks where prepared meals were accessible to consumers. Methods: The study was conducted in Mangaung Metropolitan Municipality during the winter season. Samples were collected through convenience sampling from the representative towns Thaba Nchu, Botshabelo and Bloemfontein. Using swabs, surface samples were collected and quantified from selective media. Eight beef samples were also collected; the microbial load on each sample was quantified and identified using a RapID kit. Results: The surface swabs obtained in Botshabelo (1.1 × 104 cfu/m2 - 1.1 × 106 cfu/m2) showed higher microbial counts as compared to those obtained in Bloemfontein (1.1 × 104 cfu/m2 - 1.1 × 105 cfu/m2) and Thaba Nchu (1.1 × 104 cfu/m2 - 1.1 × 105 cfu/m2). Higher microbial counts were observed on meat samples sampled in Thaba Nchu (50 cfu/g x 105 cfu/g), Bloemfontein (48 cfu/g x 104 cfu/g) and Botshabelo (33 cfu/g x 105 cfu/g) when compared to international microbiological standards. After assessing the microbial levels, Staphylococcus aureus, Escherichia coli, Candida guilliermondii, Corynebacterium jeikeium, Psychrobacter phenylpyruvicus and Peptostreptococcus tetradius were identified. Conclusion: This study confirmed contamination of surfaces and food served by vendors in Mangaung Metropolitan Municipality. The identified foodborne bacteria could pose a public health problem in each specific locality.